2016
DOI: 10.3168/jds.2015-9638
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of intake in growing dairy heifers under tropical conditions

Abstract: A meta-analysis was conducted to develop models of the prediction of dry matter intake (DMI) in growing dairy heifers [postweaning to 390 kg of body weight (BW)] under tropical conditions. The adequacy of the models was assessed in a comparison with the 4 US models currently used to predict DMI [Quigley; National Research Council; and 2 Hoffman models]. The data set was created using 95 treatment means from 28 studies published in journals. The data set (studies) was randomly divided into 2 data subsets for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 12 publications
1
25
1
Order By: Relevance
“…Therefore, milk yield and MFP are usually taken into account in models for the prediction of feed intake (Fuentes-Pila et al 1996;NRC 2001;Fox et al 2004). Dietary factors Several study showed that DMI is affected by dietary NDF concentrations (Hayirli et al 2002) and physical properties of NDF (i.e., digestibility, digestion rate and passage rate) (Oba and Allen 1998;Oliveira and Ferreira 2016). Our study also proved that dietary NDF and ADF had significant effects on variation in DMI.…”
Section: Effects Of Animal and Dietary Factors On Dmisupporting
confidence: 64%
“…Therefore, milk yield and MFP are usually taken into account in models for the prediction of feed intake (Fuentes-Pila et al 1996;NRC 2001;Fox et al 2004). Dietary factors Several study showed that DMI is affected by dietary NDF concentrations (Hayirli et al 2002) and physical properties of NDF (i.e., digestibility, digestion rate and passage rate) (Oba and Allen 1998;Oliveira and Ferreira 2016). Our study also proved that dietary NDF and ADF had significant effects on variation in DMI.…”
Section: Effects Of Animal and Dietary Factors On Dmisupporting
confidence: 64%
“…The chemical composition of diets can influence ruminants' DMI, especially the NDF content [29,30]. PM supplementation had no influence on the DMI of cows, which may due to the fact that the diets had a consistent nutritional level.…”
Section: Dmi Milk Production and Apparent Digestibilitymentioning
confidence: 99%
“…Raising replacement heifers is one of the most important steps in sustaining a milk production system (Oliveira and Ferreira, ). However, in some countries, this phase is often neglected and receives little attention (Nor et al., ).…”
Section: Introductionmentioning
confidence: 99%